Studies on Jewish and Christian historical summaries from the Hellenistic and early Roman periods - Livneh, Atar (Contributions to biblical exegesis and theology, 2019)
"This volume surveys the brief accounts of Israelite history written in Hebrew, Aramaic, and Greek between the third century BCE and the first century CE and found in compositions that did not enter the Hebrew biblical canon. Engaging in a detailed discussion of study cases and collective analysis of over forty texts, it demonstrates the affinities this category exhibits with "biblical" summaries and the influence it betrays of Hellenistic and early-Roman period literary conventions. Inter alia, the novel features it displays and new topics with which it deals, the focus it places on individual figures, and the interest it displays in the temporal axis of history reflect a process of cross-fertilization. The reviews of Israelite history that date from this period are thus hybrid artifacts that blend the conventions governing the "biblical" historical summaries with those of other literary models - such as genealogies, lists of examples, and apocalyptic historiography."--Back cover.